Biliary peritonitis. Acute kidney failure - Asiner, Boris; Dell'Oca de Fernández, M A; Turnes, Antonio (Cirugía del Uruguay, 2020)
We submit a case of bile peritonitis with acute renal failure, in the evolution of an acute litiasic colecistitis and supurative litiasic coledocitis with peritoneal síndrome. The patient was admitted with coledocian icteric síndrome. The correct diagnosis was done and the patient was operated on after a short reanimating period. We tried the primary causing lesion and the actual bile peritonitis. We have used for the post-operative therapy the osmotic diuretic "Manitol". Recovery was satisfactory. We present a brief analysis of the biochemical síndrome and tried a sinthetic commentary of the problem. The operation was done during the acute renal failure itself with simultaneous treatment of the metabolic problem.